PENGARUH INOVASI PRODUK DAN DAYA SAING TERHADAP PERKEMBANGAN UMKM DI DESA TEGALWARU CIAMPEA BOGOR - Febi , Lestari; Jamaludin, Jamaludin; Usman, Usman (An Nuqud Journal of Islamic Economics, 2025)
Micro Small and Medium Enterprises (MSMEs) have become a successful pillar of the Indonesian economy and achieved significant progress. The purpose of this study is to evaluate how competitiveness and product innovation affect the expansion of MSMEs in TegalWaru Village, Ciampea, Bogor. The method used is quantitative by applying the Slovin Formula Technique, and conducting data analysis using multiple linear regression. The results showed that product innovation and competitiveness significantly influenced the performance of MSMEs in TegalWaru Village, Ciampea, Bogor. F analysis showed a calculated F value of 86,705 with a significance of 0.000, indicating that the two independent variables, namely product innovation and competitiveness, jointly have a positive effect on the development of MSMEs. Among the two, the competitiveness variable has the most dominant influence, indicated by a calculated t value of 10.034 and a significance probability of 0.000. MSMEs are one of the pillars of the Indonesian economy that must continue to be strengthened. Thus, it can be concluded that together, product innovation and competitiveness have a significant influence on the development of MSMEs